Testing Export-Led Growth Hypothesis in Nepal Using Multivariate Cointegration Approach - Joshi, Nayan Krishna; Dahal, Madhav Prasad; Paudel, Bamadev (Economic Journal of Nepal, 2013)
Available in full text.